Performance simulation of micro hydropower system - Salam, M.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
This thesis is intended to design and implementation of analysis of micro hydropower system using computer simulation. Micro hydropower is a term used for hydroelectric system that typically produces in the 5kW to 300kW range of power. The concept in generating electricity from a potential of water flow has been around for a long time. There are many hydro electric facilities around the world that have been implemented. What is new is the idea that this concept will work on a smaller scale. For a comparison, system for the other type of renewable energy or natural resources such as wind and solar is being scale up but hydropower system is being scale down to meets community needs. It is possible and very practical to look at performance analysis of micro hydropower system using a computer simulation before implementing it in the actual condition. This thesis will provide a basic understanding of micro hydropower system development and how performance simulation of the system can be done. The information will help to determine the water potential, provide the various components necessary for a micro hydropower system, and explain the basic differences between common micro hydropower components and the best design for a micro hydropower system. This thesis also provides a valuable insight about the technique in designing micro hydropower system simulation. This thesis hopefully will be informative and enlightening.